Influence of Zirconium on the Microstructure, Selected Mechanical Properties, and Corrosion Resistance of Ti20Ta20Nb20(HfMo)20-xZrx High-Entropy Alloys - Glowka, Karsten; Zubko, Maciej; Świec, Paweł; Prusik, Krystian; Szklarska, Magdalena; Stróż, Danuta (Materials (Basel, Switzerland), 2024)
The presented work considers the influence of the hafnium and molybdenum to zirconium ratio of Ti20Ta20Nb20(HfMo)20-xZrx (where x = 0, 5, 10, 15, 20 at.%) high-entropy alloys in an as-cast state for potential biomedical applications. The current research continues with our previous results of hafnium's and molybdenum's influence on a similar chemical composition. In the presented study, the microstructure, selected mechanical properties, and corrosion resistance were investigated. The phase formation thermodynamical calculations were also applied to predict solid solution formation after solidification. The calculations predicted the presence of multi-phase, body-centred cubic phases, confirmed using X-ray diffraction and scanning electron microscopy. The chemical composition analysis showed the segregation of alloying elements. Microhardness measurements revealed a decrease in microhardness with increased zirconium content in the studied alloys. The corrosion resistance was determined in Ringer's solution to be higher than that of commercially applied biomaterials. The comparison of the obtained results with previously reported data is also presented and discussed in the presented study.
Keywords: microstructure; high-entropy alloys; multi-component alloys; corrosion resistance; mechanical properties